2018
DOI: 10.3389/fchem.2018.00037
|View full text |Cite|
|
Sign up to set email alerts
|

Ti4O7/g-C3N4 Visible Light Photocatalytic Performance on Hypophosphite Oxidation: Effect of Annealing Temperature

Abstract: The oxidation of hypophosphite to phosphate is the key to recover the phosphorus resource from the hypophosphite wastewater. In the present work, Ti4O7/g-C3N4 composites were synthesized at two different temperatures (100 and 160°C) and their performance on photocatalytic oxidation of hypophosphite under visible light irradiation and the corresponding mechanism were evaluated. A hydrolysis method using g-C3N4 and Ti4O7 was applied to synthesize the Ti4O7/g-C3N4 composites with their hybrid structure and morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Among various compositions of Ti n O 2n−1 , Ti 4 O 7 has the properties of best conductivity (1,500 S cm −1 ) and the robust resistance to aggressive chemical conditions (Ganiyu et al, 2016 ). Construction of g-C 3 N 4 /Ti 4 O 7 heterojunction significantly improved the photocatalytic performance as a result of the effective enhancement of charge separation was reported in our previous work (Guan et al, 2018 ). However, the effect of the mass ratio of Ti 4 O 7 (m): g-C 3 N 4 (m) of the g-C 3 N 4 /Ti 4 O 7 heterojunction on photocatalytic performance is still unknown.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Among various compositions of Ti n O 2n−1 , Ti 4 O 7 has the properties of best conductivity (1,500 S cm −1 ) and the robust resistance to aggressive chemical conditions (Ganiyu et al, 2016 ). Construction of g-C 3 N 4 /Ti 4 O 7 heterojunction significantly improved the photocatalytic performance as a result of the effective enhancement of charge separation was reported in our previous work (Guan et al, 2018 ). However, the effect of the mass ratio of Ti 4 O 7 (m): g-C 3 N 4 (m) of the g-C 3 N 4 /Ti 4 O 7 heterojunction on photocatalytic performance is still unknown.…”
Section: Introductionsupporting
confidence: 61%
“…The electrons on the surface of Ti 4 O 7 could easily react with O 2 adsorbed on the Ti 4 O 7 /g-C 3 N 4 surface to generate · radicals for hypophosphite oxidation. Meanwhile, the active ·OH radicals with high redox potential were generated through · radicals, which further facilitated the oxidation of hypophosphite (Nosaka and Nosaka, 2017 ; Guan et al, 2018 ). Therefore, it can be concluded that the oxidation of hypophosphite was mainly ascribed to ·OH and · radicals generated during the photocatalytic process as shown in Figure 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 284.8 eV corresponds to sp 2 -bonded C-C (Raymundo-Pinero et al, 2002). The peaks at 286.3 and 288.5 eV (Guan et al, 2018) are ascribed to C = N and N-C-N in g-C 3 N 4 respectively (Figure 3B) (Yan et al, 2012). The main peak of N 1s at 398.5 eV is assigned to sp 2 nitrogen (C=N-C) (pyridinic) present in triazine rings, while the peak at 399.6 eV arises from the tertiary nitrogen bonded to carbon atoms in the form of N–(C) 3 (pyrollic).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, electrons in the conduction band are flown through the counter electrode via the external circuit, and the holes are improved on the surface. Moreover, the induced electrons in the conduction band of PbO 2 can continually transfer to Ti 4 O 7 , and then were faster moved to the external circuit via electric field. Thus, the induced charge carriers were effectively separated.…”
Section: Resultsmentioning
confidence: 99%